2010
DOI: 10.3136/fstr.16.239
|View full text |Cite
|
Sign up to set email alerts
|

L-Lactic Acid Production from Canned Pineapple Syrup by Rapid Sucrose Catabolizing Lactobacillus paracasei NRIC 0765

Abstract: Lactic acid production from waste material has received much attention due to its sustainable utilization of biomass and the increasing demand for polylactic acid for use in biodegradable plastics. Canned pineapple syrup, a food processing waste, was utilized as a substrate for l-lactic acid production. To optimize the utilization of sucrose in pineapple syrup, in the presence of glucose and fructose, Lactobacillus paracasei NRIC 0765 was characterized and selected from 158 lactic acid bacteria strains. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Also, the intensity of growth at the 36th hour was better supported in samples with higher sugar concentrations. Nakanishi et al . noticed diauxic growth in fermentation performed on canned pineapple syrup by Lactococcus lactis at 20 g L −1 of initial sugar concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the intensity of growth at the 36th hour was better supported in samples with higher sugar concentrations. Nakanishi et al . noticed diauxic growth in fermentation performed on canned pineapple syrup by Lactococcus lactis at 20 g L −1 of initial sugar concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have confirmed the beneficial effects of pH control during production of lactic acid (Calabia & Toikwa, ; Nakanishi et al ., ; Zhang & Jin, ). There are different methods to control pH, but the simplest to employ in a small‐scale experiment without detrimental effects to the product is to neutralise the hydrogen ions as the pH drops below a set value.…”
Section: Resultsmentioning
confidence: 99%
“…The production of lactic acid are found to be 79 % yield, while only 56 % yield was produced by using solid waste. Canned pineapple syrup, a food processing waste, was utilized as a substrate for l-lactic acid production 16 . To optimize the utilization of sucrose in pineapple syrup, in the presence of glucose and fructose, Lactobacillus paracasei NRIC 0765 was characterized and selected from 158 lactic acid bacteria strains.…”
Section: Lactic Acidmentioning
confidence: 99%